Atorvastatin preoperative use in patients with coronary risk factors in major noncardiac surgery. - Alberto Labrada Despaigne; Madelín Machado Valdés; Alejandro Crespo Álvarez (ECIMED, 2016)
Introduction: Cardiovascular events are the main complication in the perioperative period. Statins are the drug of choice in primary and secondary cardiovascular disease to their lipid-lowering effect level for prevention. Objective: To determine the effect of the preoperative administration of atorvastatin in patients with coronary risk factors under major noncardiac surgery. Methods: A descriptive, prospective, randomized logitudinal in patients older than 60 years who underwent surgery at the University Hospital "General study was conducted. Calixto García "from 2011 to 2014. In all more than three coronary risk factors were identified and two groups were formed. One received a month before surgery atorvastatin 80 mg daily and another not. The variables evaluated were: TAM, FC, ST segment, QT variation and cardiovascular complications at different times. Results: Most patients were female between 65 and 74 years. The most common risk factors were hypertension, hypercholesterolemia and smoking. The TAM, FC and ST segment did not change significantly in either group. The group that received statins had a higher incidence of QT prolongation and postoperative complications of cardiovascular more significantly. Conclusions: The implementation of statin therapy in the preoperative period had a positive effect and significantly reduced morbidity and mortality intraoperatively and immediate postoperative period in these patients.